Perceptions of diversity training among medical staff - Mohd Jofaizal@Joseph, anak Entup (Universiti Malaysia Sarawak (UNIMAS), 2014)
The purpose of this research on diversity training among medical staff is to explore on the benefit and effect towards patients treatment. The researcher wishes to see whether diversity training among medical staff, can be of benefits in the treatment of patients and also for Health Care Workers to practice in their daily routine work. The design of the study is using qualitative method. The sample of this study is very small, it comprises of three informants who had vast experience in the field of health care, researcher found it most appropriate to use expert sampling technique. The instruments used in this study are guided interview questions, which comprises of at least three sections. Section ‘A’ warming up question, section ‘B’ situating question and section ‘C’ is the main question. The main finding of this study were base on the interview from the three informants, which was supported by journals and writing from prominent scholar’s. The researcher wishes to recommend that diversity training among medical staff should be continued and sustain. All this training can improve skills and competency of various categories of health care workers, but it needed the strong support from the Ministry Of Health. Diversity training is a course of instruction aimed at increasing the participant’s cultural awareness, knowledge, and skills in order to benefit organizations.